Management of possible stroke by laypeople in pre-hospital setting: who should we train? - Stirparo, Giuseppe; Kacerik , Erika; Ristagno , Giuseppe; Andreassi, Aida; Coppo, Anna; Migliari, Maurizio; Albonico, Andrea; Sechi, Giuseppe Maria; Zoli, Alberto; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: The pre-hospital management of a possible stroke is fundamental for the transport of patients to the correct HUB facility; thus, they must be transported to the Emergency Department (ED) by EMS vehicles. Our study aims to analyze the factors correlated with a higher probability of accessing the ED through the EMS in this event. Methods: This is a retrospective observational study. All accesses in the 120 EDs of the Lombardy region, with a diagnosis of discharge whose symptoms could resemble CPSS, were analyzed between 1 January 2019 and 31 December 2019. Results: We identified an increased probability of using the EMS vehicles of 0,05% (I.C. 95%: 0.04% - 0.06%; p<0.0001) for each additional year of age, considering patients aged 20 to 100 years and the percentage was significantly higher in the female population (58% vs 49%; p<0.001). Moreover, we calculated that the incidence of stroke was approximately 140 cases per 100,000 inhabitants. Conclusions: Only half of the citizens in the Lombardy region use the EMS in case of suspicion of stroke; further information campaigns are essential to educate citizens. Information strategies should be directed especially at men between 30 and 59 years old.